Preventing inadvertent perioperative hypothermia in adults - Juda, Małgorzata; Małodobry, Katarzyna; Ozga, Dorota (Journal of Education, Health and Sport, 2018)
Inadvertent perioperative hypothermia is a serious clinical problem, which could lead to the development of serious complications that prolong hospital care and increase medical costs. Anesthesia, surgery and microclimate in the operating room contributes to impaired physiological mechanisms of thermoregulation and thus the development of hypothermia in the patient. Therefore, it is essential that personnel responsible for the safety of perioperative patient had knowledge of the principles of maintaining normothermia and applied in clinical practice.